Uncaria tomentosa and topical sse in genital herpes in vulva: case report - Passos, Mauro Romero Leal; Geller, Mauro; Barreto, Nero A.; Passos, Mariana D.L.; Passos, Felipe D.L.; Varella, Renata Q. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: genital herpes is a sexually transmitted infectious disease that affects people from many different social strata. Genital herpes is spread worldwide and is a frequent cause of painful genital sores in men and women. Objective and Methods: to describe the case of adult women with clinical and cytologic clinical picture of a vulvar initial outbreak of genital herpes in which the lesion was treated with Uncaria tomentosa gel 50 mg/g three times a day for four days. Results: the symptoms of pain and burning had rapid remission. During the consultation, about 25 minutes after topical application of the herbal medicine, the patient reported great improvement in genital pain. The clinical outcome was satisfactory and after six days the patient, whose lesion had already healed, reported having had vaginal intercourse without discomfort. Conclusion: application of Uncaria tomentosa topical gel in a vulvar initial outbreak of genital herpes was well tolerated, showed no side effects, and rapidly and significantly improved the clinical symptoms of disease.